Cost benefit analysis of the implementation of an occupational health and safety management system based on the productivity of the company Electrocons Ingenieros S.A. - Malpartida Córdova, Yeni Miriam (2022)
The  purpose of this research was related to carrying out a cost-benefit analysis of the application of a method to implement a Health and Safety Management System at work, with the intention of increasing the production rates of the Electrocons Ingenieros SA company, as a tool to promote a safer work environment, which will allow the worker to detect with suspicion, the presence of occupational accidents and achieve better results in the employees, by classifying risk factors in which they are exposed the worker and generate occupational accidents according to the evolution of the activities carried out in the company Electrocons Ingenieros SA This research is based on authors such as Cortés Díaz (2018), Koontz et al. (2012), International Labor Organization (OIT, 2019),  Muñoz Romero (2014) and Martínez Gómez (2015). It was based on non-experimental studies and has a cross-sectional and correlational design. The population was 40 employees, with a sample of thirty-six (36) employees. For data collection, unstructured observation, notes and photographic memory were used after visiting the Electrocons Ingenieros SA facilities, which revealed that the establishment of an Occupational Health and Safety Management System (OHSMS), which had a positive influence on obtaining added value to the productivity variable of the company Electrocons Ingenieros SA